Nypa fruticans Wurmb. Vinegar’s Aqueous Extract Stimulates Insulin Secretion and Exerts Hepatoprotective Effect on STZ-Induced Diabetic Rats - Yusoff, Nor Adlin (Nutrients, 2017)
Background: An aqueous extract (AE) of vinegar made from Nypa fruticans Wurmb. can improve postprandial glucose levels in normoglycaemic rats. The aim of this study was to evaluate its antihyperglycaemic activity further using in vivo and in vitro approaches. Methods: AE was administered to streptozotocin (STZ)-induced diabetic rats twice daily at three doses (1000, 500, and 250 mg/kg b.w.) for 12 days p.o. Several biochemical analyses and a histological study of the pancreas and liver were performed, accompanied by a cell culture assay. Results: As compared to diabetic control (DC), AE at the doses of 500 and 1000 mg/kg b.w. caused significant reduction (p < 0.05) of blood glucose, total cholesterol and triglycerides levels, with positive improvement of serum insulin levels. Interestingly, immunohistochemical staining of the pancreas suggested no β-cell regeneration, despite significant increase in insulin production. AE-treated groups, however, showed overall restoration of the hepatic histoarchitecture of STZ-induced liver damage, suggesting a possible hepatoprotective effect. The pancreatic effect of AE was further studied through RIN-5F cell culture, which revealed a positive stimulatory effect on insulin release at a basal glucose concentration (1.1 mM). Conclusion: Nypa fruticans Wurmb. vinegar’s aqueous extract exerts its antihyperglycaemic activity, at least in part, through insulin stimulatory and hepatoprotective effects.